2016
DOI: 10.1016/j.colsurfa.2015.10.063
|View full text |Cite
|
Sign up to set email alerts
|

An effective method for improving electrocoagulation process: Optimization of Al 13 polymer formation

Abstract: h i g h l i g h t s• Al 13 polymer formation in EC process are investigated.• Al 13 species fraction positively correlated with removal of turbidity and organic.• pH 5-7 and lowering j favored the formation of Al 13 polymer.• Al 13 fraction can reach more than 60% under optimal EC conditions. Keywords: Electrocoagulation Aluminum species Electrochemical parameter a b s t r a c t Al 13 polymer has been believed to be the most active species responsible for coagulation. The character of Al species distribution a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The results of BET analysis implied that the flocs generated at low initial pH may have more surface adsorption sites, which would make EC perform better at low pH condition. Moreover, in-situ Al 13 polymer could be generated in EC process, and became the dominant species at about 5 min in the weak acidic pH condition [23]. The flocs generated from Al 13 polymer showed a larger flocs size and a rougher surface structure than other Al species [21].…”
Section: Role Of Flocs In Ha Removalmentioning
confidence: 93%
See 1 more Smart Citation
“…The results of BET analysis implied that the flocs generated at low initial pH may have more surface adsorption sites, which would make EC perform better at low pH condition. Moreover, in-situ Al 13 polymer could be generated in EC process, and became the dominant species at about 5 min in the weak acidic pH condition [23]. The flocs generated from Al 13 polymer showed a larger flocs size and a rougher surface structure than other Al species [21].…”
Section: Role Of Flocs In Ha Removalmentioning
confidence: 93%
“…5e), and it was consistent with the results of BET analysis. According to our previous results [23], low j and weak acidic water conditions favored the formation of in-situ Al 13 polymer. A lot of studies [20,21] have demonstrated that the flocs generated from Al 13 polymer are looser and more porous surface.…”
Section: Flocs Structure and Morphology Analysismentioning
confidence: 99%
“…In situ , trivalent iron is formed by hydroxylation, forming Fe (OH) 3 . The iron oxidation and Cr (VI) reduction reactions are favoured at low pH 46 . The formation of a pH-lowering microenvironment on the colloidal surface (Pac-02) and a proton-transferring microinterface process can control the formation of intermediates with different degrees of polymerization of Al through Al(OH) 3 + H + , and the cationic polymer polyacrylamide (PAM) could be used as a coagulant aid 47 .…”
Section: Discussionmentioning
confidence: 99%
“…It justifies why supporting electrolytes in electrocoagulation studies should contain a chaotrope anion rather than a kosmotrope anion to allow a favorable release of aluminum cations. + after sufficient aging [37,38]. For pH values lower than 5, A l 3+ cations are the sole ionic species in aqueous phase, they gradually disappear in favor of cationic hydroxides in the pH range 5-7.5.…”
Section: Tablementioning
confidence: 99%